Transgenic Ectopic Overexpression of Broad Complex (BrC-Z2) in the Silk Gland Inhibits the Expression of Silk Fibroin Genes of Bombyx mori - Jiangshan Cong; Cuicui Tao; Xuan Zhang; Hui Zhang; Tingcai Cheng; Chun Liu (Insects, 2020)
Bombyx mori silk protein genes are strictly turned on and off in different developmental stages under the hormone periodically change. The broad complex (BrC) is a transcription factor mediating 20-hydroxyecdysone action, which plays important roles during metamorphosis. Here, we observed that two isoforms of BmBrC (BmBrC-Z2 and BmBrC-Z4) exhibited contrasting expression patterns with fibroin genes (FibH, FibL and P25) in the posterior silk gland (PSG), suggesting that BmBrC may negatively regulate fibroin genes. Transgenic lines were constructed to ectopically overexpress BmBrC-Z2 in the PSG. The silk protein genes in the transgenic line were decreased to almost half of that in the wild type. The silk yield was decreased significantly. In addition, the expression levels of regulatory factors (BmKr-h1 and BmDimm) response to juvenile hormone (JH) signal were inhibited significantly. Then exogenous JH in the BmBrC-Z2 overexpressed lines can inhibit the expression of BmBrC-Z2 and activate the expression of silk protein genes and restore the silk yield to the level of the wild type. These results indicated that BmBrC may inhibit fibroin genes by repressing the JH signal pathway, which would assist in deciphering the comprehensive regulation mechanism of silk protein genes.